Dense and strong, but superinsulating silica aerogel. (July 2021) - Iswar, Subramaniam; Galmarini, Sandra; Bonanomi, Luca; Wernery, Jannis; Roumeli, Eleftheria; Nimalshantha, Sudheera; Ben Ishai, Avner M.; Lattuada, Marco; Koebel, Matthias M.; Malfait, Wim J.
Abstract: Silica aerogel is the ultimate thermal insulator thanks to its record-breaking low thermal conductivity (λ), open porosity and hydrophobicity. Silica aerogel's thermal conductivity is lowest at intermediate densities (ρ ≈ 0.11 g/cm 3 ) and, because of the strong, power-law dependence of the E modulus on density, this rather low density so far led to low E moduli. Even with polymer reinforcement, increasing stiffness is only possible at higher density, thus higher conductivity. This paper explores the synthesis of silica aerogel granules using ambient pressure drying to provide enhanced mechanical stiffness whilst maintaining thermal conductivities well below 20 mW m −1 K −1 . The aging and drying conditions affect the interplay between mechanical and thermal properties, and are varied to optimize the physical properties. The dense (ρ≤0.29 g/cm 3 ), but superinsulating (λ≈15 mW m −1 K −1 ) silica aerogels presented in this paper challenge the community's understanding of heat transport in aerogels, and do not rely on polymer reinforcement. The underlying microscopic structural parameters affecting the mechanical and thermal transport properties are investigated by modelling and simulation of the aerogel back-bone. Short aging times reduce the cross-section of, and heat transport through, inter-particle necks, leading to an overall decrease in thermal conductivity through the solid skeleton (λs ). In addition, short-aged gels undergo a partial pore collapse during ambient pressure drying of the pore fluid due to less aged, hence weaker network structures. The resulting denser structure contains additional point contacts that increase stiffness, by up to an order of magnitude. However, heat transport through these newly formed point-contacts is limited and the gas phase conduction (λs ) is further suppressed due to the even smaller pore sizes. Strong and superinsulating particles are ideal fillers for aerogel composites, concrete and renders. The optimized APD aerogels, available as granules, are finally compiled in a composite thermal insulation board with an effective thermal conductivity down to 20 mW m −1 K −1 with improved strength: a 2-fold increase for E, compared to a board produced from classical silica aerogel granulate. The possibility to improve mechanical properties of pure silica aerogels can help aerogels to break into new high-strength, superinsulating structural applications needed to reduce carbon emissions of the built environment.